Effect of lean six sigma on quality performance in Malaysian hospitals - Ahmed, Selim; Manaf, Noor Hazilah; Islam, Rafikul (Emerald Publishing Limited, 2018)
Purpose – The purpose of this paper is to investigate the effects of Lean Six Sigma (LSS) and workforce management on the quality performance of Malaysian hospitals. This paper also investigates the direct and indirect relationships between top management commitment and quality performance of the healthcare organisations in Malaysia. Design/methodology/approach – This study applied stratified random sampling to collect data from 15 different hospitals in Peninsular Malaysia. The self-administered survey questionnaires were distributed among 673 hospital staff (i.e. doctors, nurses, pharmacists, and medical laboratory technologists) to obtain 335 useful responses with a 49.47 per cent valid response rate. The research data were analysed based on confirmatory factor analysis and structural equation modelling by using AMOS version 23 software. Findings – The research findings indicated that LSS and workforce management have a significant impact on quality performance of the Malaysian hospitals, whereas senior management commitment was found to have an insignificant relationship with quality performance. The research findings indicate that senior management commitment has no direct significant relationship with quality performance, but it has an indirect significant relationship with quality performance through the mediating effects of LSS and workforce management. Research limitations/implications – This research focussed solely on healthcare organisations in Malaysia and thus the results might not be applicable for other countries as well as other service organisations. Originality/value – This research provides theoretical, methodological, and practical contributions for the LSS approach and the research findings are expected to provide guidelines to enhance the level of quality performance in healthcare organisations in Malaysia as well as other countries.